IDENTIFICATION OF CDNA FRAGMENT TIGHTLY LINKED TO NV AND TM-2 LOCI IN TOMATO - , Sobir; Fusao Motoyoshi (Zuriat, 2005)
Tm-2 is a resistance gene in tomato to Tomato Mosaic Virus (ToMV), located in heterochromatic region of chromosome nine. Since map based cloning difficult to perform for identify the gene on that region, we apply differential display approach by using two near-isogenic tomato lines (NILs), one without Tm-2 and the other with Tm-2 to identify cDNAs of the transcripts from the region surrounding the Tm-2 locus. Among the 150 combinations of three anchor primers and fifty arbitrary primers, 10 combinations generated cDNA polymorphic bands. Out of them, only one combination of CA6, exhibited polymorphic band under southern blot analysis, subsequently a genetic experiment showed that the CA6 locus tightly linked to the Tm-2 locus. The CA6 fragment also hybridized to genomic DNA fragments from a tomato line carrying Tm-2a, a line of L. peruvianum from which Tm-2a originated, and a tomato line carrying another Tm-2-like gene. A northern hybridization blotting result suggested that the gene corresponding to CA6 fragment was constitutively transcribed.